Role of zinc oxide nanoparticles supplementation on alleviate side effects of cisplatin induced cardiotoxicity in rats - A. M. Al-lbban (Brazilian Journal of Biology)
Abstract Cisplatin is one of the most potent chemotherapeutics for treating a wide range of tumor forms. Its use is severely limited due to cause cardiotoxicity. The goal of this investigate estimated the proactive effect of ZnONPs against cardiotoxicity induced by cisplatin (CP). The rats were classed as control-positive (group two), and different groups from third to seventh were given one milliliter of individually dosed ZnONPs at 10, 20, 30, 40, and 50 mg/kg daily and compared with control negative group (group one). Atherogenic indices (AC, CRR, and AI), lipid peroxidation, heart tissue antioxidant enzymes, cytokines, and specific serum biomarkers lipid profiles (TC, TG, HDL, and LDL), and kidney functions were assessed in serum at the ending of the biological experimental. Findings were in view that these parameters improved gradually when the doses of ZnONPs in the various rat groups were increased to 50 mg/kg/day/bw. Measurements of pro-inflammatory, antioxidant, and oxidant biomarkers in heart tissue also showed that, at a dose of 50 mg/kg/day, the various rat groups progressively recovered to a level equivalent to that of the healthy control group. This clarifies why ZnONPs guard against heart tissue injury. It was determined that ZnONPs, with a more marked improvement, considerably reduced oxidative stress, suppressed inflammation, and inhibited apoptosis, thereby improving cisplatin-induced heart damage.